The Collateral School and Legal Pedagogy as a means of teaching-learning in Law School (Revista científica Olimpia, 2023)
With the aim of contributing to the strengthening and paradigmatic change, we undertook this research, which is based on the use of the Collateral School and Legal Pedagogy as a path towards a transformation of teaching in the Law School. We present this document with the intention of addressing the edges that Legal Pedagogy as a Science encompasses in the field of university education. Integrating the importance of the school environment, which constitutes the experience of the student and the teacher as part of learning during the teaching-learning process.
Keywords: Pedagogy; Law; Collateral School; teaching; learning